Drivers for differences in dairy farmers' perceptions of farm development strategies in an area with nature and landscape as protected public goods. (August 2016) - Methorst, Ron; Roep, Dirk; Verhees, Frans; Verstegen, Jos
Nature and landscape are increasingly appreciated as public goods and community assets in need of protection. Policy schemes aiming to protect vulnerable nature and landscape assets affect options for farm development and thus the opportunities for farm income strategies. Farmers as small business owners need to counter an ongoing income squeeze in their strategic decision. Farmers' perception of the options affects strategic decision making. In a case study with dairy farmers operating in a highly comparable biophysical and socio-economic context, farmers differed in the perception leading to three main income strategies: 'maximising' or 'ending' of milk production and 'diversification of farm business' with the most dominant strategy being 'maximising'. Multiple regression analysis was used to explore the significance of seven drivers for the differences between farmers' perception of farm development options. The 'personal views and preference' is the most significant explanatory driver for all three income strategies. 'View on markets' is of less significance and 'view on urban-rural relation' is not significant in explaining differences between farmers. 'Maximising' and 'diversifying' are opposites in their drivers. To increase the effectiveness of policy schemes and support programmes, personal views and preferences of farmers need to be taken into account.